Aging, blade tenderization, and enzyme injection impacts tenderness of muscles from fed cull cows of known age - Hutchinson, Stacy L.; Marston, T.T.; Hunt, Melvin C.; Unruh, John A. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Approximately 16% of the 31 million head of cattle harvested in the United States in 2005 were aged cows. Cow meat is known to be tougher than meat from young steers and heifers, and it typically has a less desirable, darker color. It is generally assumed that cow meat needs to be ground or have some form of postmortem tenderization applied to be merchandized as a whole muscle product. The knuckle, top sirloin, and top blade muscles have been identified as muscles that potentially can be upgraded to medium-priced steaks. Most cow steaks are fabricated by food-service providers for their customers with different specifications for aging and post-mortem tenderization application. Aging, blade tenderization, and injection enhancement are commonly used on cow meat to increase tenderness. It is unknown if extended aging is needed in addition to the other two methods to improve tenderness. If shorter aging periods can be used without compromising an improvement in tenderness, then aging costs would be greatly reduced. Our objective was to determine the effects of days of aging on tenderness of cow steaks from the knuckle, top sirloin, and top blade that were blade tenderized and injected with an enhancement solution containing an enzyme tenderizer.
Keywords: Beef; Cattle; Tenderizing; Cull cows